Development Planning Study of Oil Palm in Malang Regency - Tarno, Hagus; Nugroho, Agus; Devi, Mia Prastika; Yahya, Minhajul Qowim; Karuniawan, Anggik; Anggraeni, Alifia Nurma; Wicaksono, Karuniawan Puji; Hermawan, Romy; Meinardhy, Ricky; Ramayanti, Kinta; Pamungkasih, Estri; Ristanti, Rahmadina Fitria; Wahyudie, Diyan Eko; Arin, Iftita Yustitia (Journal of Innovation and Applied Technology, 2025)
Malang District, East Java, presents significant potential for the development of oil palm plantations due to its favorable climate and land conditions. Indonesia, as the world's largest producer of palm oil, benefits from this industry, which contributes notably to its GDP and job creation. This study aims to provide a comprehensive development plan for oil palm in Malang District, incorporating environmental, economic, and social considerations. A participatory, data-driven approach was employed, combining field surveys, stakeholder interviews, and GIS mapping to assess land suitability, market dynamics, and environmental risks. The study's findings highlight the potential for enhancing oil palm productivity while addressing environmental and social concerns through sustainable practices and certifications like ISPO and RSPO. Economic analysis demonstrates the profitability of integrated oil palm management, with recommendations for improving operational efficiency, waste management, and market access.